Rapid CD8+ Function Is Critical for Protection of Neonatal Mice from an Extracellular Bacterial Enteropathogen - Siefker, David T.; Adkins, Becky (Frontiers in Pediatrics, 2017)
Both human and murine neonates are characteristically highly susceptible to bacterial infections. However, we recently discovered that neonatal mice are surprisingly highly resistant to oral infection with Yersinia enterocolitica. This resistance was linked with activation of both innate and adaptive responses, involving innate phagocytes, CD4+ cells, and B cells. We have now extended these studies and found that CD8+ cells also contribute importantly to neonatal protection from Y. enterocolitica. Strikingly, neonatal CD8+ cells in the mesenteric lymph nodes (MLN) are rapidly mobilized, increasing in proportion, number, and IFNγ production as early as 48 hr post infection. This early activation appears to be critical for protection since B2m-/- neonates are significantly more susceptible than wt neonates to primary Y. enterocolitica infection. In the absence of CD8+ cells, Y. enterocolitica rapidly disseminated to peripheral tissues. Within 48 hr of infection, both the spleens and livers of B2m-/-, but not wt, neonates became heavily colonized, likely leading to their deaths from sepsis. In contrast to primary infection, CD8+ cells were dispensable for the generation of immunological memory protective against secondary infection. These results indicate that CD8+ cells in the neonatal MLN contribute importantly to protection against an extracellular bacterial enteropathogen but, notably, they appear to act during the early innate phase of the immune response.